High‐commitment work systems and middle managers' innovative behavior in the Chinese context: The moderating role of work‐life conflicts and work climate - Chen, Yang; Jiang, Yan J.; Tang, Guiyao; Cooke, Fang L. (Human Resource Management, 2018)
This study advances research on high‐commitment work systems (HCWSs) and organizational innovation by examining how the configuration of middle managers' work–family issues (i.e., work–family conflict and work climate for sharing family concerns) shape the relationship between HCWSs and innovation performance. Using a matched sample of senior management team members, middle managers, and frontline employees from 113 Chinese manufacturing firms and two waves of survey, we found that HCWSs are associated with enhanced levels of middle managers' innovative behavior, an association that improves innovation performance. The results also show that high levels of work–family conflict weaken the relationship between HCWSs and innovative behavior, but can be attenuated when a work climate better facilitates the sharing of family concerns. The study contributes to the knowledge of the role of HCWSs and contextual conditions of their effects in enhancing organizational innovation performance, with specific implications for the Chinese context.